The Influence of Project Work Approach on College Students’ Interest in Programming at the Private Universities in Ghana - Ampofo, Isaac Atta Senior; Ampofo, Isaac Atta Junior (Universitas Sebelas Maret, 2022)
Failure rates have become a global problem as university students studying computer programming grow worldwide. Students' interest has been linked to learning skills that require metacognition and critical thinking, which are essential for studying computer programming efficiently. As a result, the project work approach in studying computer programming combines knowledge of technology with soft skills. Project work is best suited for complicated problem-solving tactics and teamwork creatively. The study used quantitative methodology and a descriptive design survey to evaluate the project work approach's influence on college students’ interest in programming. The study's participants were Christian Service University computer science students. A total of 420 students were enrolled in the study, with a sample size of 368. Inferential and descriptive statistics were applied to analyze the data received from the respondents. The study found that standalone systems were the highest factor in the project work given to students. The study revealed that project work could make students interested in programming. The study concluded that project work has a favorable and considerable impact on college students' programming interests.